BUSINESS MODEL CANVAS, COPYWRITING AND CREATIVE CONTENT TRAINING FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN TUBAN - Novyandri Taufik Bahtera; Andi Estetiono; Moh. Darus Salam (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: The problem faced by Micro, Small and Medium Enterprises (MSMEs) in Tegalagung Village, Semanding District, Tuban Regency is the lack of attractive product descriptions and information displayed on social media and marketplace platforms that they already have. In addition, MSMEs also find it difficult to determine the value proposition of the product so that it is difficult to differentiate themselves from their competitors and cannot compete in the market. MSMEs are also not right in determining their market segments, fostering poor relationships with customers and partners, and determining product distribution channels that are still wrong. Objective: This activity aims to provide solutions from problem descriptions and unattractive product information and product value identification by providing Copywriting and Creative Content and Business Model Canvas (BMC) training to make product descriptions and information more attractive so that consumers can make transactions. purchasing and Identifying and compiling 9 components of BMC. Methods: Participants were explained about the function of copywriting in making social media statuses more attractive, captions on Instagram, and interesting articles/content on the website. In addition, participants were explained about content marketing using AIDA theory, namely Attention, Interest, Desire and Action. Results: The participants gained increased knowledge and understanding in terms of preparing the Business Model Canvas and Creative Content and Copywriting for businesses. Conclusion: The community service program has obtained the expected results, namely MSME actors can identify and create their Business Model in the correct BMC format.